2009
DOI: 10.1111/j.1365-2052.2008.01824.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for performance traits in a broiler × layer cross

Abstract: An F(2) resource population, derived from a broiler x layer cross, was used to map quantitative trait loci (QTL) for body weights at days 1, 35 and 41, weight gain, feed intake, feed efficiency from 35 to 41 days and intestinal length. Up to 577 F(2) chickens were genotyped with 103 genetic markers covering 21 linkage groups. A preliminary QTL mapping report using this same population focused exclusively on GGA1. Regression methods were applied to line-cross and half-sib models for QTL interval mapping. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 28 publications
8
79
1
14
Order By: Relevance
“…However, few studies have investigated the genetic background of small intestine development. Previous studies have reported quantitative trait loci (QTL) in animal intestines (Ambo et al 2009;Gao et al , 2010Mignon-Grasteau et al 2015). Of these, Gao et al (2010) identified 10 QTL for the length of small intestine associated with growth traits in a F 2 population of a cross between White Duroc  Chinese Erhualian pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have investigated the genetic background of small intestine development. Previous studies have reported quantitative trait loci (QTL) in animal intestines (Ambo et al 2009;Gao et al , 2010Mignon-Grasteau et al 2015). Of these, Gao et al (2010) identified 10 QTL for the length of small intestine associated with growth traits in a F 2 population of a cross between White Duroc  Chinese Erhualian pigs.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, QTL were detected at an intestine length of 481 cM (GGA1) in an F 2 population derived from an intercross of White Plymouth Rock with Silkie chickens, which suggested an association with intestinal length ). In an F 2 generation derived from a broiler  layer cross, one QTL on GGA4 was associated with intestinal length (Ambo et al 2009). Seven genome-wide significant QTL were found for duodenum length (DL), jejunum length (JL) and ileum length (IL) in F 2 chickens from a cross between D À and D þ chickens fed a wheat-based diet (Mignon-Grasteau et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some QTLs mapped in this population have been described by Nones et al (2006), Ambo et al (2009) and Campos et al (2009). Procedures seeking to reduce the occurrence of false positives or negatives were not employed in these studies, except of course to adjust the level of type I error to an acceptable level.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Nones et al (2006) mapped QTL for carcass and BW42 traits on GGA1, in the same broiler population. Ambo et al (2009), studying the same population of broilers, mapped QTL for body weight traits at 35 and 41 days of age on the GGA4, exactly in the same chromosome region where QTL for tibia width and weight were mapped (MCW0240-LEI0063). Within this chromosome region, Baron et al (2011) mapped QTL for drums and thighs; Schreiweis et al (2005) for tibia area, length, and width; and Sharman et al (2007) for tibia bone mineral density, and femur weight.…”
Section: Quantitative Trait Loci Mappingmentioning
confidence: 99%
“…The population was designed specifically for QTL mapping studies, to obtain linkage disequilibrium and variability for performance and carcass traits (Nones et al, 2006;Ambo et al, 2009;Savegnago et al, 2011).…”
Section: Experimental Populationmentioning
confidence: 99%